ANALISIS PERUBAHAN PERILAKU SEKSUAL IBU MENOPAUSE TERHADAP TINGKAT KEPUASAN SUAMI DALAM MELAKUKAN HUBUNGAN SEKSUAL DI DESA LEDUG KECAMATAN KEMBARAN BANYUMAS - Noor Yunida Triana; Ana Rufaida (Universitas Harapan Bangsa Purwokerto, 2012)
This study aims to understand the influence of sexual behavior changes mother withmenopause against husband gratification in Ledug village, Banyumas Regency. Thisstudy used cross sectional approach to measure the relationship between two variables.Sample collection used purposive technical sampling with inclusion and exclusionspecific criteria. Respondent in this research consisted of 60 spouse who lived in LedugVillage. Chi square analyze showed si gni f i cant relation of sexual behavior changes tohusband gratification with p value = 0.034. There are relation between behavior changesmother with menopause and husband gratification in Ledug village. Keyword : sexual behavior changes, menopause mother, husband gratification.